Study of WZ production with the D0 detector - Kaadze, Ketino (Kansas State University, 2010)
In this Dissertation I present a detailed study of ppbar->WZ production using fully leptonic decays of W and Z bosons with electrons and muons in the final state. Data used for the study were collected by the D0 detector at the Fermilab proton-antiproton collider with a center-of-mass energy of 1.96 TeV and correspond to 4.1 fb[surepscript]-1 of integrated luminosity. The most precise measurement of the WZ production cross section is obtained and found to be in a good agreement with the standard model prediction. I also present a search for new phenomena in the WZ production by investigating the coupling between W and Z bosons and by searching for new charged particles that can decay into WZ boson pair. No evidence for new physics is found, and the most stringent limits are set on the anomalous WWZ coupling parameters and masses of charged resonances. This result also sets the stringest limit on one of the possible sources of electroweak symmetry breaking, a low-scale Technicolor with a typical heavy techni-pion hypothesis.
Keywords: WZ production; Tevatron and LHC; new physics; cross section; couplings; Physics, Elementary Particles and High Energy (0798)